The Impact of Internal Communication and Work Environment on Employee Performance in Manufacturing Companies in Semarang - Ruth Desna Sari Dachi; Krisnawati Setyaningrum Nugraheni (Badan Penerbit STIEPARI Press, 2025)
This study analyzes the effect of internal communication and work environment on employee performance in manufacturing companies in Semarang, Indonesia. Using a quantitative survey method with 103 respondents, data were collected via Likert-scale questionnaire and analyzed using multiple linear regression. Results show that both internal communication and work environment significantly influence employee performance. Work environment has a more dominant effect (β = 0.779) than internal communication (β = 0.168). The model explains 86.8% of performance variance (R² = 0.868), demonstrating strong predictive power. This study provides practical recommendations for manufacturing managers to prioritize work environment improvements while maintaining effective communication systems. It contributes to human resource management literature by establishing the relative importance of environmental versus communication factors in manufacturing contexts.